The influence of communicative strategies on enhancing the reading proficiency of 6th grade students at Francisco Gárate School. Proposal: develop a didactic guide to improve the reading skills of 6th grade students at Francisco Gárate School. - Pincay Pita, Steven Javier (2024)
PDF